2016
DOI: 10.1109/toh.2016.2571694
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile Force Perception – Absolute and Differential Thresholds and External Influences

Abstract: Three experiments were carried out to determine absolute and differential thresholds for vibrotactile forces and external influences in the frequency range of 5 to 1,000 Hz at the tip of the index finger. Differential thresholds were obtained for reference stimuli of 0.5, 0.25 N, and near the individual threshold. Frequency, temperature, age, fingertip size, and contact force were investigated as parameters in a full-factorial design. Experiments were conducted with at least 27 subjects and a 1up-2down stairca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…8). We used the human sensitivity functions reported in [42], [43] for the force, acceleration and displacement data, respectively. Moreover, we calculated the corresponding electrostatic forces generated by the same waveforms and amplitudes via Matlab simulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8). We used the human sensitivity functions reported in [42], [43] for the force, acceleration and displacement data, respectively. Moreover, we calculated the corresponding electrostatic forces generated by the same waveforms and amplitudes via Matlab simulations.…”
Section: Discussionmentioning
confidence: 99%
“…We collected force and acceleration data from fingertips of the subjects while they explored a touch screen displaying electrovibration stimuli at threshold voltages. We analyzed the collected data in frequency domain by taking the human tactile sensitivity curves given in [42], [43] into account. The results suggested that Pacinian was the primary psychophysical channel in the detection of the square wave input signals tested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This was either because of limited relevance in the design of task‐specific haptic interfaces (sex, fingertip size, manual dexterity), to lower the number of factor level combinations (temperature was set to 23°C in the room where experiments took place), or in favor of a worst‐case‐approximation (only young subjects were included in the study who exhibit lower thresholds compared with older people). The contact force between finger and contactor, that exhibits strong influences on the mechanical impedance, was not considered, since previous studies by the authors did not find significant effects on perception parameters . The effect of the contact area size is thoroughly described in the existing literature, the combination with wearing a glove does not give grounds to expect any additional effects on the perception thresholds.…”
Section: Methodsmentioning
confidence: 99%
“…The contact force between finger and contactor, that exhibits strong influences on the mechanical impedance, was not considered, since previous studies by the authors did not find significant effects on perception parameters. 18 The effect of the contact area size is thoroughly described in the existing literature, 19 the combination with wearing a glove does not give grounds to expect any additional effects on the perception thresholds. Therefore, it is not considered in this study.…”
Section: Experimental Designmentioning
confidence: 99%
“…Therefore, to compensate for the limitation of the haptic sense to perceive frequency variations, we did not rely on the haptic frequency shift alone to represent the notes of the highlighted instrument. We took advantage of the noticeable capabilities of the somatosensory sense to distinguish small amplitude variations (1.7~19 mN for frequencies at 320Hz) (Hatzfeld, Cao, Kupnik, & Werthschtzky, 2016), so the waveform characteristics of the highlighted instrument were also included in the haptic signal envelope.…”
Section: Haptic Stimulusmentioning
confidence: 99%